Nome waterfront, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: John J. Sesnon co., Barracks Square, Nome Life Saving Station, Miners & Merchants Bank. 4039 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number